Pertumbuhan Ekonomi dan Kemiskinan Indonesia: Analisis Dampak Liberalisasi Perdagangan pada Mitra Dagang Utama - Neli Aida; Feri Dwi Riyanto (Jurnal Akuntansi, Keuangan, dan Manajemen, 2021)
Purpose: This study aimed to analyze the effect of trade liberalization on Indonesia's exports by involving the three (South Korea, Japan, and China) major trading partner countries. Research Methodology: This study used the concept of a gravity model, with panel data samples from 1996 - 2019. This study used independent variables such as tariffs, level of openness, exchange rates, poverty, economic growth (GDP), inflation, and distance. Results: The study results found that tariffs and the level of openness have a significant effect on exports. It can be said that trade liberalization has an effect on exports. In addition, the variables GDP, poverty, and the exchange rate also have a significant effect on exports. Meanwhile, the two variables of inflation and distance have no effect on Indonesian exports. This condition shows the same thing among the three trading partner countries. Limitations: Other elements were not included in this study, such as digitalization and international trade technology. Contribution: The theoretical contribution of this research provides scientific contributions in the field of economic liberalization and poverty, and the empirical contribution shows that Indonesia's macroeconomic conditions are still dependent on trade with neighboring countries.